Breast Milk Antibody Levels in Tdap-Vaccinated Women After Preterm Delivery. (26th March 2021) - Orije, Marjolein R P; Larivière, Ynke; Herzog, Sereina A; Mahieu, Ludo M; Van Damme, Pierre; Leuridan, Elke; Maertens, Kirsten
Abstract: Background: Enrichment of breast milk (BM) with immunoglobulin (Ig) A and IgG through maternal vaccination could help infants combat targeted pathogens. However, evidence on this effect after preterm delivery is lacking. In this study, we investigated the total and anti-pertussis toxin (anti-PT)–specific IgA and IgG production in BM after term and preterm delivery in the presence of maternal Tdap (tetanus, diphtheria, acellular pertussis) vaccination. Methods: Serum and BM samples of lactating women who delivered at term or prematurely and did or did not receive Tdap vaccine (Boostrix, GSK Biologicals) during pregnancy were collected as part of a clinical study (N = 234). Anti-PT IgA/IgG (IBL assay; Meso Scale Discovery assay) and total IgA/IgG (Thermofisher, on BM samples only) immunosorbent assays were performed on all samples collected at 72 hours and 4, 8, and 12 weeks postpartum. Results: BM after preterm delivery contained anti-PT IgA and IgG geometric mean concentrations (GMCs) comparable to those after term delivery (eg, colostrum anti-PT IgA, 5.39 IU/mL vs 6.69 IU/mL, respectively). Maternal Tdap vaccination induced significantly higher anti-PT IgG GMCs in colostrum of vaccinated compared with unvaccinated women who delivered at term (0.110 IU/mL vs 0.027 IU/mL, P = .009). Anti-PT antibodies persisted up to 12 weeks postpartum. Conclusions: This study provides evidence that maternal Tdap vaccination induces high Ig levels in BM after both term and preterm delivery and that these antibodies remain abundantly present throughout lactation, possibly offering additional mucosal protection during the most vulnerable period in early life. Clinical Trial Registration: NCT02511327. Abstract : Maternal tetanus, diphtheria, acellular pertussis vaccination induces comparable pertussis toxin (PT) immunoglobulins (Igs) in breast milk (BM) after both term and preterm delivery. BM PT Igs remain detectable up to 12 weeks postpartum. High BM PT Igs could offer additional mucosal immunity against Bordetella pertussis .